Development Of Interactive Presentation Media Wudhu Material Using Inner Canva Learning Islamic Religious Education - syafii, herman; Saleh, Muhammad; Ahdar; Usman; Marhani (Al-Iftah: Journal of Islamic studies and society, 2024)
The aims of this research is to develop interactive presentation media regarding ablution material using Canva. The intention of developing presentation media is to simplify the educators in delivering learning materials more attractively. This research is conducted by adopting the 4-D development model modified according to the researcher's needs and capabilities, including the steps (Definition, Design, Development, and Dissemination). The developed presentation media used Canva. The developed media that has undergone expert and material validation tests, was then limitedly trailed on 5 students as well on a larger scale with 18 randomly selected fourth-grade students at SD Negeri 47 Parepare. The result of this study is an interactive presentation media regarding ablution material using Canva. Based on the final validity assessment by media validators, it achieved a score of 85.29%, categorized as good. The material validation test achieved a final score of 97,06%, categorized as very good. Furthermore, to measure the students’ responses, the researcher delivered a small-scale trial scored 81%, categorized as good, and a large-scale trial scored 90.55%, categorized as very good. Therefore, it can be assumed that the interactive presentation media toward ablution material using Canva developed in this research is viable to be used in Islamic education learning toward ablution material for fourth-grade students at SD Negeri 47 Parepare.